Aktivitas Senyawa Antioksidan Daun Labu Kuning (Cucurbita maxima Duch.) - Harmida; Salni; Desti Amanda Pratiwi; Nita Aminasih; Singgih Triwardana (Jurnal Biosilampari : Jurnal Biologi, 2024)
This study aimed to determine the activity and class of antioxidant compounds in pumpkin leaves. The research methods carried out were refining pumpkin leaves simplicia, extraction, fractionation, antioxidant activity test with TLC plate, purification, determination of compound class, and antioxidant activity test using the Difenilpikril Hidrazil Hidrat (DPPH) method. The results showed that the active fraction of pumpkin leaves is the ethyl acetate fraction, and the n-hexane fraction, column chromatography on the active fraction obtained six pure eluates that have antioxidant activity, namely N1, N2, E1, E2, and E3. Groups of compounds N1, N2, E1 are terpenoids, group E2 eluates compounds are flavonoids, while E3 eluates are included in the tannin group. The pure eluate antioxidant activity test with the DPPH method obtained IC50 values of N1 are 25.02 ppm, N2 36.27 ppm and E1 40.04 ppm, E2 68.10 ppm and E3 105.38 ppm.